PENYULUHAN PENTINGNYA KEBERSIHAN LINGKUNGAN DI DESA MUARA SANDING KECAMATAN GARUT KOTA - Hasbi Taobah Ramdani; Asep Nidzar Faidjurahman; Anry Sutrisno; Dede Suharta (Jurnal Pengabdian Masyarakat DEDIKASI, 2020)
A clean and well-maintained environment will have a good impact on the health of residents in the area in Muara Sanding Village, therefore there needs to be an effort to improve the cleanliness of the environment. The method of implementing this community service activity is health counseling which takes place in Kp.Sanding Lebak with 36 participants present. Counseling on the importance of maintaining a clean and healthy environment is a theme in this community service. The results of this community service show that residents are enthusiastic about participating in activities, besides that residents also increase their knowledge about the definition of clean, clean characteristics, types of cleanliness, benefits of cleanliness, aspects needed to realize cleanliness and the consequences if not maintaining cleanliness.